2015
DOI: 10.11113/jt.v73.4291
|View full text |Cite
|
Sign up to set email alerts
|

A Review on The Exploration of Nanomaterials Application in Pavement Engineering

Abstract: In order to improve the performance of asphalt mixture, the virgin asphalt binder needs to be modified with suitable modifiers. There are various types of modifiers available in market and it is clearly stated and established in most of pavement standard specification. Nowadays, pavement technologist and researchers had put their interests on nanotechnology and they had found that polymeric nanocomposites have shown its effectiveness through the modification of virgin asphalt binder with certain portion of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In principle, WMA technology could reduce asphalt binder viscosity, which allows the asphalt binder to achieve optimal viscosity for coating with the aggregate. This ensures that the mixing and compaction processes could be done at lower temperatures without adversely affecting its performance when compared to conventional hot-mix asphalt (HMA) [1][2][3][4][5]. Blankendaal et al [6] reported that, by using the life http://dx.doi.org/10.1016/j.conbuildmat.2016.03.068 0950-0618/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 96%
“…In principle, WMA technology could reduce asphalt binder viscosity, which allows the asphalt binder to achieve optimal viscosity for coating with the aggregate. This ensures that the mixing and compaction processes could be done at lower temperatures without adversely affecting its performance when compared to conventional hot-mix asphalt (HMA) [1][2][3][4][5]. Blankendaal et al [6] reported that, by using the life http://dx.doi.org/10.1016/j.conbuildmat.2016.03.068 0950-0618/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 96%
“…Nano materials are distinguished by having a size smaller than 100 nm in diameter, developed by methods of synthesis of materials in gaseous, liquid or solid state, which are generally sought to have a morphology, chemical composition, microstructures and purity desired for the application of different technologies in the field of chemistry, biomedical, electronics and others [16], [17]. Table I shows the different types of structures that can be achieved in the field of nano materials and their fabrication methods that are currently under development, which initially have a high cost due to the fabrication equipment, but are compensated throughout the life span of the works [18].…”
Section: Nanotechnology In the Construction Sectormentioning
confidence: 99%
“…In order to mitigate flooding risks and related damages, the initiative of sponge cities has been widely enforced, where the construction of permeable pavements has emerged as one of the effective alternatives to enhance drainage capacity of urban road networks [ 4 , 5 , 6 ]. As compared to traditional impervious or low-permeability pavement structures constructed with dense-graded materials, permeable pavement layers constructed with open-graded materials feature larger porosity and better-connected pore structure, as well as the resulting advantages of improved drainability, skid resistance, and sound-absorbing and noise-reducing abilities [ 7 , 8 , 9 , 10 , 11 ]. As tunneling rock wastes (TRWs) are being increasingly produced and stockpiled, the sustainable recycling and reuse of such open- or gap-graded waste materials in permeable pavement construction becomes a major socioenvironmental concern and thus deserves in-depth research efforts.…”
Section: Introductionmentioning
confidence: 99%